Navigating policy challenges in Malaysia’s construction sector: The governmental dilemma on the issue of foreign labour shortage in Malaysia - Saari, Mohd Nasir; Shuib, Md Shukri; Ajis, Mohd Na’eim (International Journal of Asian Social Science, 2024)
This study examines the challenges associated with Malaysia’s reliance on foreign labour, particularly in the construction sector. It investigates how governmental policies respond to labour shortages while balancing national economic needs and social impacts. A qualitative research methodology involved an in-depth analysis of policy documents and thematic interviews with key stakeholders, including policymakers and industry representatives. The study explores the dynamics of foreign labour employment policies, focusing on inter-sectoral competition for workers and the implications of policy shifts on workforce stability. The research highlights the persistent labour shortage in the construction sector, exacerbated by local workers’ reluctance to engage in "3D" jobs (dirty, dangerous, and difficult) and the competition from the agricultural and plantation sectors for foreign labour. The government’s decision to allow foreign workers to switch employers temporarily alleviates labour shortages but poses challenges to policy consistency. Inter-ministerial cooperation between the Ministry of Home Affairs (MoHA) and the Ministry of Human Resources (MoHR) is identified as a critical strategy to harmonise labour needs with national development goals. The findings underscore the need for cohesive policy frameworks that address labour shortages while minimising negative socio-economic impacts. Recommendations include enhanced inter-agency collaboration, structured workforce planning, and incentives to attract local workers to underrepresented sectors, which support sustainable development in Malaysia.